Sustainable development and management of medical tourism companies in Poland - Anna Maria Wiśniewska (International Journal of Management and Economics, 2021)
The aim of the paper is to analyze the macroeconomic sector of medical tourism and to demonstrate through empirical research the possibilities of using business opportunities for the development of medical tourism in Poland. The thesis is to point out that development of companies in medical tourism is one of the components of metropolises' sustainable development.
Keywords: MO1; 650; medical tourism; sustainable development of metropolises